Knowledge, attitude, and practice of kangaroo mother care among doctors in a tertiary care hospital from North India - Singh, Anita; Mishra, Namita; Gupta, Girish (Indian Journal of Child Health, 2018)
Introduction: Kangaroo mother care (KMC) has been established as having an important role in the care of all the babies; especially, the preterm and low birth weight babies. Successful implementation of KMC depends on knowledge, attitude, and practice (KAP) of healthcare workers, mothers, fathers, and other family members. Objectives: The objectives of the study ws to determine the KAP of KMC among the faculty and residents of the departments of neonatology and obstetrics in a tertiary care hospital. Methods: The study was a cross-sectional descriptive study in which data were collected from departments of neonatology, maternal health, and reproductive health. The study subjects were faculty and residents from both the departments. They were interviewed using a structured pre-tested questionnaire in three domains, knowledge (11), attitude (8), and practice (4). The responses were tested against standard predefined answers and were expressed in percentages. Results: A total number of 25 doctors were interviewed; among knowledge domain, approximately 60% doctors responded correctly for the need of KMC, duration of KMC, feeding during KMC and type of baby’s clothes during KMC. In the domain of attitude, response of KMC for who can give, when to start/stop, position of mother, and feasibility of KMC during non-invasive ventilation was correct for all subjects. For practice aspect, there was a lack of counseling and re-checking, though almost everyone felt the need of separate KMC room and counselor. Conclusions: From the above results, it is apparent that knowledge and attitude, among health-care professionals, is optimum. However, there is lots of scope for filling a few gaps to improve practices and training workshops are required to bring in behavior change among doctors.